The Impact of Islam on Arab Thought - Hammadi, Hammad Farhan; Indo Santalia; Abdullah; Muhsin (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
The Arabs before Islam had an advanced civilization, such as the Mesopotamian Civilization in Iraq and the Nile Valley Civilization in Egypt. Additionally, there were kingdoms in the Arabian Peninsula and the Levant. They possessed qualities that prepared them to receive and convey the divine message, as Allah says: You are the best nation produced [as an example] for mankind (Ali Imran: 110). However, Allah also described some of their behaviors as "jahiliyyah" (ignorance), not in the sense of lack of knowledge, but ignorance of divine laws, such as worshiping idols. Islam came to reform Arab society and build a righteous community. One of its major reforms in religion was the call to monotheism and the abandonment of idol worship, along with the establishment of hudud laws, ethical transactions, and lawful work. Islam also made zakat obligatory to combat greed and assist the poor, prohibited usury, and regulated inheritance to ensure justice. Additionally, Islam fought against exploitation and extravagance and supervised state officials to prevent corruption. In the field of knowledge, Islam encouraged the pursuit of learning, reflection, and contemplation, as stated in Allah’s words: Read in the name of your Lord who created (Al-‘Alaq: 1-5). Politically, Islam united the Arabs who were previously divided and under Byzantine and Persian colonization. The Prophet Muhammad SAW issued the Charter of Medina, which established rules for shared governance. Islam brought a significant transformation to the mindset of the Arabs, shifting them from tribal fanaticism to religious and political unity. This facilitated the establishment of an Islamic state that rapidly expanded to reach the borders of China. The tolerant teachings of Islam united beliefs and social systems between Arabs and other nations, making the Arabs the bearers of Islam to the entire world.